Perancangan Arsitektur Enterprise Untuk Digital Maritim Development Center(DMDC): Studi Kasus PT Integrasi Logistik Cipta Solusi (ILCS) - Octaviani, Shella; Purwandari, Betty P; Satria, Riri; Trisnawaty, Ni Wayan (The Indonesian Journal of Computer Science, 2025)
Technological advancements in the port sector present significant challenges for the Digital Maritime Development Center (DMDC) in supporting the digital transformation of PT Integrasi Logistik Cipta Solusi (ILCS). The absence of an integrated Enterprise Architecture (EA) hinders DMDC's ability to design and manage digital initiatives, resulting in suboptimal alignment between technology components and business processes. This study aims to design an EA aligned with ILCS's business strategy using The Open Group Architecture Framework (TOGAF). The research approach involves analyzing business needs, conducting interviews, reviewing documents, and designing architecture across business, application, data, and technology domains. The outcome is an EA design that enhances operational efficiency, system interoperability, and continuous innovation. This study is expected to provide strategic guidance for DMDC in solidifying its role as a leading center for digital solutions development in Indonesia's maritime logistics sector.